SELF-PROTECTION BEHAVIORS TOWARDS COVID-19 AMONG WOMEN RELIGIOUS GROUP IN INDONESIA: A QUALITATIVE STUDY - Raihana Nadra Alkaff; Lisfa Sentosa Aisyah; Dieta Nurrika; Ratri Ciptaningtyas (IAKMI South Tangerang Branch, 2022)
Abstract Background: Optimizing the role of religious-based communities in preventing the transmission of COVID-19 through the application of self-protection to its facilitators and members is an important part of efforts to stop the pandemic. Objective: The purpose of this study was to determine the perceptions of facilitators and members of religious group in implementing self-protection behaviour. Method: A qualitative study was conducted from August to December 2021 using a purposive sampling approach to collect the data. In total, 6 individual interviews were conducted with facilitators of religious group and one focus group discussion (FGD) with 12 members of religious-based communities. Data analysis was performed using a conventional content analysis approach. Results: The results of this study indicate that both facilitators and members of religious-based communities have a favourable perception of self-protection in religious group. However, this perception is not enough to support readiness in implementing self-protection behaviour. Self-efficacy is still weak, this is indicated by weaknesses in mastery experiences, vicarious experiences, verbal persuasion, and emotional and physiological states variables. Conclusion: Increasing int ernal and external roles in religious-based communities and strengthening collaboration in the application of self-protection through increasing self-efficacy forming variables in religious group are urgent needs to be carried out in COVID-19 prevention programs.